Review on conductivity an under-developed method to detect milk adulteration (International Journal of Food and Nutritional Sciences, 2022)
Milk adulteration is an issue that is continuously increasing. Milk adulteration is done to gain more profits. A general issue of adulteration of any food arises when demand is more than supply. There are many milk adulteration methods. Water adulteration is not only the adulteration used in milk but urea, detergent, foreign fat, neutralizer, flour, and many other methods are used. A single method is not sufficient to detect milk adulteration. However, conductivity and the dielectric property of milk are two main parameters that have been explored for a long time for the detection of milk adulteration. This paper discusses the research works which explored conductivity as a parameter to detect the different types of milk adulteration.